The implementation of promotional mix in reaching Mesiniaga Berhad’s target market / Aiman Zarif Analiz - Analiz, Aiman Zarif (Faculty of Business and Management, 2010)
Promotions are a vital stage of marketing in conducting a business. It is one of the 4Ps elements. The promotional mix is the elements in promotions which are advertising, direct marketing, sales promotions, public relations and personal selling. Every element has different impacts than the other elements. Businesses normally would not use only one of the elements but would have combinations of several of the elements.